2011
DOI: 10.1002/erv.1132
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Perception in Patients with Eating Disorders in Comparison with Depressed Patients

Abstract: Eating disordered patients and DP showed alterations of emotional perception of anger, an emotion which is closely linked to interpersonal difficulties. Alterations in emotional perception of EDP and DP might be due to more general emotion regulation disturbances. In order to detect more subtle differences between psychiatric subgroups, more sophisticated investigation tools are needed. Increased disgust ratings in DP merit further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 52 publications
1
21
0
1
Order By: Relevance
“…The BMI of obese women was 43.2 ± 8.1 kg/m 2 , which was higher compared with the other groups (means: NWC 21.3 kg/m 2 , bulimia nervosa 22.2 kg/m 2 , and anorexia nervosa 16.3 kg/m 2 ) (Joos et al, ). The mean age was 45.6 ± 10.9 years (comparison groups: means 24.0–27.4 years).…”
Section: Resultsmentioning
confidence: 93%
“…The BMI of obese women was 43.2 ± 8.1 kg/m 2 , which was higher compared with the other groups (means: NWC 21.3 kg/m 2 , bulimia nervosa 22.2 kg/m 2 , and anorexia nervosa 16.3 kg/m 2 ) (Joos et al, ). The mean age was 45.6 ± 10.9 years (comparison groups: means 24.0–27.4 years).…”
Section: Resultsmentioning
confidence: 93%
“…This region also activates during successful self-inhibition of loss-chasing in pathological gamblers (Campbell-Meiklejohn et al, 2008), and during food cravings (Kober et al, 2010) and cigarette cravings in smokers (Brody et al, 2007). It has also recently been shown to be hypoactive during the viewing of food cues in patients with BN (Joos et al, 2011). If the DMPFC is important for the successful inhibition of impulses to binge and purge, then rTMS-induced enhancement of its activity may explain the rapid remission of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…To date, few studies have examined the use of rTMS in patients with eating disorders, and results have been mixed using the conventional rTMS target in the dorsolateral prefrontal cortex (DLPFC; Hausmann et al, 2004; Walpoth et al, 2008; Van den Eynde et al, 2010). However, neuroimaging studies in eating disorders suggest structural and functional abnormalities of other regions, such as the anterior cingulate cortex and the neighboring dorsomedial prefrontal cortex (DMPFC; Muhlau et al, 2007; Schafer et al, 2010; Joos et al, 2011), suggesting that these could be more effective rTMS targets. Of note, there is also a converging body of evidence from lesion, stimulation, morphometric, and functional connectivity studies highlighting the DMPFC as a critical nexus of structural and functional pathology in MDD, suggesting that the DMPFC may be an effective rTMS target for MDD as well (Stefurak et al, 2003; Koenigs et al, 2008; Koenigs and Grafman, 2009; Sheline et al, 2010; Bora et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous research found that the left medial prefrontal cortex (mPFC) of BN patients were significantly activated in response to negative body-image words and suggested that the mPFC is associated with the functional abnormalities of brain systems in BN patients [21]. Joos et al [22] substantiates a key role of lateral prefrontal dysfunction, which is a brain region involved in impulsive control, in BN patients. The binge eating/purging group showed significantly greater activations of the bilateral precentral gyrus, anterior cingulated cortex (ACC), and middle and superior temporal gyrus than healthy groups during a response inhibition task [23].…”
Section: Introductionmentioning
confidence: 95%